Relief systems handbook - Parry, Cyril F. (Institution of Chemical Engineers ; Distributed exclusively in the USA and Canada by VCH, 1992)
Annotation This practical guide fills a gap in the literature on pressure relief design, operation and maintenance, covering the applicability to and reliability of different pressure relief devices in individual situations.
Keywords: Chemical plants -- Safety measures -- Handbooks, manuals, etc.; Relief valves -- Handbooks, manuals, etc.; elektronické knihy; electronic books